Kindly give a step-by-step solution and the person who will give the correct answer will be marked as a brainliest. (answer-121/16)
Attachments:
![](https://hi-static.z-dn.net/files/d5c/02b5779440535c3da553bd321376e145.jpg)
Answers
Answered by
0
Answer:
answer in the attachment is the answer of your one of the question..
Attachments:
![](https://hi-static.z-dn.net/files/d50/8025617e89dbc0955518f4ceb0661d80.jpg)
![](https://hi-static.z-dn.net/files/d95/56a90546c8f135fb3a101018bcd7eff6.jpg)
Answered by
0
LET THE NUMBER BE = x
Now,
(4/9)^-5 * x = (2/3)^-2
=>(9/4)^5 * x = (2/3)^-2 [the minus is removed by inverting the fraction]
=>(3/2)^5*2 * x = (2/3)^-2
=>(3/2)^10 * x = (2/3)^-2
=> x = (2/3)^-2 * (2/3)^10 [ the fraction becomes inverted as it comes to other side of the equal to sign without any equal stimulant]
=> x = (2/3)^-2+10
=> x = (2/3)^8
=> x= 256/6561
therefore the answer is 256/6561 or (2/3)^8
Similar questions
Math,
3 months ago
Science,
3 months ago
English,
6 months ago
Social Sciences,
1 year ago
Science,
1 year ago